Gastrointestinal Bleeding in a Patient With Gastric Lymphoma, Tuberculosis Enteritis, and Cytomegalovirus Enteritis. Issue 2 (20th February 2020) - Castillo, Gabriel; Argyropoulos, Kimon; Moen, Farnoush M.; Bhakta, Dimpal
ABSTRACT: Bleeding from the small bowel can be challenging to identify by endoscopic or radiographic evaluation. We present the case of a patient with incompletely treated latent tuberculosis and medical history of T-cell lymphoma who developed gastrointestinal bleeding because of concurrent Burkitt lymphoma, tuberculosis enteritis, and cytomegalovirus enteritis. The interplay of these 3 diagnoses is discussed.